Advancement in fiber reinforced polymer, metal alloys and multi-layered armour systems for ballistic applications – a review - Bhat, Aayush; Naveen, Jesu; Jawaid, Mohammad; M. N. F., Norrrahim; Rashedi, Ahmad; Khan, Anish (Elsevier, 2021)
The recent research and development performed for armour systems for material selection and analysis has helped discover new and significant material properties suited for ballistic applications. The realm of ballistic studies has employed advanced materials to provide the desired performance, considering the strict requirement of perfect material selection for armour systems. Energy absorption, ballistic limit, and depth of indentation are the most important parameters to be analyzed for an efficient armour system. The importance of utilizing appropriate materials for armour system is necessary, to achieve higher energy absorption, ballistic limit, and low blunt trauma (<44 mm), while simultaneously ensuring the armour has low weight. The aim of this review is to analyze the different armour systems such as fiber reinforced polymeric composites, metallic and multilayer armour systems (MAS) to understand their response on ballistic impact. Also, the importance of advanced fabrication techniques such as bio-inspired fabrication and additive manufacturing for armour applications has been addressed in detail. Moreover, this review critically analyzed the possible ways to enhance the ballistic performance of fiber reinforced polymeric composites, metallic materials, and MAS.